Second Hankel Determinants for Some Subclasses of Biunivalent Functions Associated with Pseudo-Starlike Functions. (4th December 2017) - Laxmi, K. Rajya; Sharma, R. Bharavi
Abstract : We introduce second Hankel determinant of biunivalent analytic functions associated with λ -pseudo-starlike function in the open unit disc Δ subordinate to a starlike univalent function whose range is symmetric with respect to the real axis.